PROSES PENCIPTAAN KOMPOSISI MUSIK KYAI BADRANAYA DALAM KARYA MUSIK KIDUNG SEMAR - Setyoko, Aris; Supanggah, Rahayu (Fakultas Ilmu Budaya, Universitas Mulawarman, 2018)
Kyai Badranaya is another name for figures in the purwa puppet show which is a symbolic figure for Javanese people. The special symbolic means to have variations, concepts of life, and beliefs in Javanese society. In the Javanese purwa puppet show, Semar figures are representations of good and wise qualities in human beings. Real Semar figures are also gods who transformed into commoners and became servants, protectors, and also knights of Pandawa namely Yudhistira, Bima, Arjuna, Nakula, and Sadewa in the Javanese version of the Mahabharata epics. The musical composition of Kyai Badranaya is part of the four musical compositions of Kidung Semar by the author, who presents musical performances with ideas from the values and semar phenomenon of Semar figures in the purwa puppet show in Java. The method is carried out through stages, namely the alignment process, and sound training. With this method, the music composition of Kyai Badranaya is compiled and presented in the form of a musical repertoire, which proposes reflection and thoughts about how one becomes a leader who applies the life concept of Semar, namely tepa selira, lembah manah, and andhap asor. The purpose of various organizations is the application used as a learning medium for the general public in the form of new music works. The result of the creation of this musical composition work is to contribute scientific thinking on how to create new music works by utilizing work from traditional sources of Javanese musical music in particular, as well as archipelago music.